2020
DOI: 10.1186/s12879-020-05006-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of multi-drug resistant Campylobacter spp. and residual antimicrobials at poultry farms and live bird markets in Bangladesh

Abstract: Background: Understanding potential risks of multi-drug resistant (MDR) pathogens from the booming poultry sector is a crucial public health concern. Campylobacter spp. are among the most important zoonotic pathogens associated with MDR infections in poultry and human. This study systematically examined potential risks and associated socio-environmental factors of MDR Campylobacter spp. in poultry farms and live bird markets (LBMs) of Bangladesh. Methods: Microbial culture and PCR-based methods were applied to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 41 publications
8
35
2
Order By: Relevance
“…The drinking water of 18.8% (12/64) poultry farms was found to be contaminated with Campylobacter. The result obtained from this study was corroborated by another research conducted in Bangladesh as presence of 33% Campylobacter contamination in drinking water samples from broiler farms [21]. The present study further confirmed as 18.8% (12/64) farm attendants' hand rinsed water were found to be Campylobacter positive as they were exposed to contaminated flocks and water or even poultry cages during working at the farms.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The drinking water of 18.8% (12/64) poultry farms was found to be contaminated with Campylobacter. The result obtained from this study was corroborated by another research conducted in Bangladesh as presence of 33% Campylobacter contamination in drinking water samples from broiler farms [21]. The present study further confirmed as 18.8% (12/64) farm attendants' hand rinsed water were found to be Campylobacter positive as they were exposed to contaminated flocks and water or even poultry cages during working at the farms.…”
Section: Discussionsupporting
confidence: 86%
“…However, use of protective materials like mask and gloves, aprons are needed that will minimize further exposure of zoonotic pathogens [47,48]. Likewise, the study confirmed 20.3% (13 in 64) feed samples found to be positive with Campylobacter that disagrees with the other research as 0% Campylobacter positive status confirmed [21]. Since the feed sampling was accomplished using the pool samples (both from feeder and stored feed) from the surveyed farms, this positivity status of the feed sample due to cross contamination from the infected feeds at poultry feeder.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…strains resistant to ciprofloxacin, tetracycline, and erythromycin is increasing (GarcĂ­a-FernĂĄndez et al, 2018). A tendency to detect increasing multidrug-resistant (MDR) strains has been reported in both humans (Feizabadi et al, 2007) and food-producing animals (Li et al, 2016;Neogi et al, 2020). The potential risk of MDR Campylobacter spread from animals to human is of great concern.…”
Section: Introductionmentioning
confidence: 99%